Numerical Modeling of the Internal Dispersive Shock Wave in the Ocean - Tatiana Talipova; Efim Pelinovsky; Oxana Kurkina; Andrey Kurkin (Shock and Vibration)
Numerical modeling of dispersive shock waves called solibore in a stratified fluid is conducted. The theoretical model is based on extended version of the Korteweg-de Vries equation which takes into account the effects of cubic nonlinearity and Earth rotation. This model is now very popular in the physical oceanography. Initial conditions for simulations correspond to the real observed internal waves of shock-like shape in the Pechora Sea, the Arctic. It is shown that a sharp drop (like kink in the soliton theory) in the depth of the thermocline is conserved at a distance of one–three kilometers, and then it is transformed into dispersive shock waves (shock wave with undulations).